Development of science e-modules with the STEM (Science, Technology, Engineering, and Mathematics) approach for islamic schools - Masykur, Ruhban; Irwandani, Irwandani; Pricillia, Agitha; Aridan, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2024)
The current development of education demands students to compete globally with modern technological knowledge. This research aims to develop a science e-module with the STEM approach embedded with religious values for students of madrasas, pesantren, and integrated Islamic schools. The research method used is research and development with the ADDIE model. Data were collected through observation, interviews, documentation, and questionnaires, which were then analyzed using qualitative and quantitative approaches. The results of the material expert validation reached 93% (excellent), and media expert validation reached 92% (excellent). This e-module is considered practical with a practicality test result by educators of 81% (excellent) and attractive according to users with a test score of 80% (very attractive). This module integrates religious values within the science material using the STEM approach to stimulate students and support science learning in the context of Islamic education. This research has implications for developing technology-based learning materials in Islamic educational institutions.